On an open question in the inverse transmission eigenvalue problem. (27th February 2015) - Buterin, S A; Yang, C-F; Yurko, V A
Abstract: We prove that eigenvalues (with their multiplicities) do not uniquely determine in the boundary value problem as well as in the problem under the condition This result gives an answer to the open question raised by Aktosun et al (2011 Inverse Problems 27, 115004 ). The proof is constructive.